Digital Watermarking Based on DWT (Discrete Wavelet Transform) and DCT (Discrete Cosine Transform) - Hazim Barnouti, Nawaf; Saeb Sabri, Zaid; L. Hameed, Khaldoun (International Journal of Engineering and Technology, 2019)
Digital watermarking is a technique to secure privacy of digital information and itâ€™s an important research area. There is a high risk in piracy with technology developments. Therefore, digital watermarking methods are necessary to solve the problem of content authentication and copyright protection. Digital data is available such as images and videos. The increased value of digital content makes new challenges to secure the digital media. Several digital watermarking methods are actually proposed in special domain and transforms domain. Spatial domain methods still have relatively low-bit capacity. Frequency domain-based methods are more robust and can embed more bits for watermark. watermarking in the frequency domain includes: Discrete Cosine Transform (DCT) and Discrete Wavelet Transform (DWT). In this work, digital watermarking method for embedding and extraction copyright protection based on DWT and DCT is proposed. The two methods taking benefit from the advantages of both techniques and make one hybrid method. The combined method is applied on two-dimensional images (original cover image and watermark image). This watermarking method provides good performance and strong robustness.Â Â